A systematic review of robotic-assisted unicompartmental knee arthroplasty: prosthesis design and type should be reported. (July 2019) - Robinson, P. G.; Clement, N. D.; Hamilton, D.; Blyth, M. J. G.; Haddad, F. S.; Patton, J. T.
Abstract : Aims: Robotic-assisted unicompartmental knee arthroplasty (UKA) promises accurate implant placement with the potential of improved survival and functional outcomes. The aim of this study was to present the current evidence for robotic-assisted UKA and describe the outcome in terms of implant positioning, range of movement (ROM), function and survival, and the types of robot and implants that are currently used. Materials and Methods: A search of PubMed and Medline was performed in October 2018 in line with the Preferred Reporting Items for Systematic Review and Meta-Analysis statement. Search terms included "robotic", "knee", and "surgery". The criteria for inclusion was any study describing the use of robotic UKA and reporting implant positioning, ROM, function, and survival for clinical, cadaveric, or dry bone studies. Results: A total of 528 articles were initially identified from the databases and reference lists. Following full text screening, 38 studies that satisfied the inclusion criteria were included. In all, 20 studies reported on implant positioning, 18 on functional outcomes, 16 on survivorship, and six on ROM. The Mako (Stryker, Mahwah, New Jersey) robot was used in 32 studies (84%), the BlueBelt Navio (Blue Belt Technologies, Plymouth, Minnesota) in three (8%), the Sculptor RGA (Stanmore Implants, Borehamwood United Kingdom) in two (5%), and the Acrobot (The Acrobot Co. Ltd., London, United Kingdom) in one study (3%). The most commonly used implant was the Restoris MCK (Stryker). Nine studies (24%) did not report the implant that was used. The pooled survivorship at six years follow-up was 96%. However, when assessing survival according to implant design, survivorship of an inlay (all-polyethylene) tibial implant was 89%, whereas that of an onlay (metal-backed) implant was 97% at six years (odds ratio 3.66, 95% confidence interval 20.7 to 6.46, p < 0.001). Conclusion: There is little description of the choice of implant when reporting robotic-assisted UKA, which is essential when assessing survivorship, in the literature. Implant positioning with robotic-assisted UKA is more accurate and more reproducible than that performed manually and may offer better functional outcomes, but whether this translates into improved implant survival in the mid- to longer-term remains to be seen. Cite this article: Bone Joint J 2019;101-B:838–847.